Integrated Model of Traceability (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
In last few years, the problem of food safety is becoming bigger while consumers' awareness regarding social responsibility in production, distribution and consumption of food is growing. The main goal for food enterprises is to provide food traceability. This paper focus on traceability systems that can be used to attain the food safety through the systematic monitoring of physical movement of food related raw materials and finished products. In this paper, integrated model of traceability, based on three layers is presented. Our intention is to present concept of traceability which enterprises can use to ensure food safety and food tracking, while traceability concept refers to timely monitoring and accurate recording of product modification process through time and space.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.